2020
DOI: 10.1212/wnl.0000000000010955
|View full text |Cite
|
Sign up to set email alerts
|

Thrombectomy vs medical management in low NIHSS acute anterior circulation stroke

Abstract: BackgroundEndovascular thrombectomy (EVT) is highly effective for acute ischemic stroke with large vessel occlusion (LVO) and moderate to severe neurologic deficits.ObjectiveTo undertake an effectiveness and safety analysis of EVT in patients with LVO and NIHSS ≤6 using datasets of multicentre and multinational nature.MethodsWe pooled patients with anterior circulation occlusion from 3 prospective international cohorts. Patients were eligible if presentation occurred within 12 hours from last known well and ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 34 publications
2
32
0
1
Order By: Relevance
“…Dargazanli and coworkers have shown that patients with anterior circulation LVO and minor-to-mild symptoms (baseline NIHSS score < 8) have an excellent outcome after MT more often than those left on BMM, despite an increase rate of brain bleeding events [32]. On the other hand, a more recent multicenter study by Volny and coworkers, that included patients with occlusion of ICA and/or MCA (M1 and proximal M2 segments), has shown that MT was associated with a 8.6% higher chance of excellent outcome but with a 22.3% higher risk of neurological deterioration at 24 h and a 2.2% higher risk of death of any cause within 90 days [33].…”
Section: Discussionmentioning
confidence: 99%
“…Dargazanli and coworkers have shown that patients with anterior circulation LVO and minor-to-mild symptoms (baseline NIHSS score < 8) have an excellent outcome after MT more often than those left on BMM, despite an increase rate of brain bleeding events [32]. On the other hand, a more recent multicenter study by Volny and coworkers, that included patients with occlusion of ICA and/or MCA (M1 and proximal M2 segments), has shown that MT was associated with a 8.6% higher chance of excellent outcome but with a 22.3% higher risk of neurological deterioration at 24 h and a 2.2% higher risk of death of any cause within 90 days [33].…”
Section: Discussionmentioning
confidence: 99%
“…Here, the occlusion site may be of importance (7). Nevertheless, only limited evidence from retrospective data exists regarding the efficacy of MT (8,9), also in comparison to initial medical management with rescue intervention in case of secondary deterioration (10)(11)(12). However, mild stroke symptoms may not justify immediate MT in view of the procedure's invasiveness and potential serious adverse effects (13).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, most of these patients may be denied a proven therapy due to low NIHSS scores [95,96]. Recently, retrospective studies have shown higher odds of improved outcomes for EVT in patients with LVO and NIHSS ≤ 5 [96][97][98]. Two multicenter clinical trials, ENDLOW (Endovascular Therapy for Low NIHSS Ischemic Strokes) trial (NCT04167527) in North America and MOSTE (Minor Stroke Therapy Evaluation) trial (NCT03796468) in Europe, are investigating the efficacy of EVT in patients with anterior circulation LVO and NIHSS ≤ 5 or 4, respectively.…”
Section: Thrombectomy Beyond 24 Hoursmentioning
confidence: 99%